Consumer Preferences in Choosing Online Food Delivery Services in Jakarta - Ramon Hurdawaty; Kenny Dylun (The Postgraduate School of Tourism Sahid Polytechnic, 2024)
Purpose: This research aims to determine consumer preference factors when purchasing Jakarta's online food delivery services. Research methods: This study uses a comparative quantitative method. Data was obtained by distributing online questionnaires via Google form to 100 users of Online Food Delivery Services (Grab-Food et al.) in Jakarta. In this study, the sample was determined by purposive sampling. Researchers conducted a one-way ANOVA test to see if there were differences in respondents' preferences. The preference factors used are transaction, price, and promotion. Results and discussion: Research has been conducted to understand consumer preferences in popular food delivery services such as Go-Food, GrabFood, and ShopeeFood. Understanding these preferences is critical for companies to tailor their services and offerings to meet their customers' needs and expectations better. The research results show differences in consumer preferences when choosing online food delivery services. Implication: By leveraging this research, all stakeholders can contribute to a more competitive, user-friendly, and innovative food delivery landscape. Go-Food, Grab-Food, and Shopee-Food can continue to innovate, develop transaction systems so that users are more comfortable making transactions when using the Food Delivery Service application, provide prices according to the quality provided, and take a more innovative and creative promotional approach so that many users can know the promotion. Keywords: Online Food Delivery Service, Preference, Go-Food, Grab-Food, Shopee-Food